Waveguides for neurostimulation in the cochlea - Kim, Matthew; Cury, Joaquin; Kessler, Lexie; Triplett, Michael; Sahota, Sarah; Kampasi, Komal; Tan, Xiaodong; Haque, Razi-ul; Richter, Claus-Peter (Frontiers in Audiology and Otology, 2024)
Optical stimulation has been suggested for neural stimulation to improve cochlear implants. Light allows more spatially selective activation of neuron populations than electrical current. More independent frequency bands along the spiral ganglion are available to encode acoustic information with an anticipated better frequency resolution and a better cochlear implant user performance in noisy listening environments, tonal languages, and music perception. Optical cochlear implants (oCIs) can deliver light either directly via small emitters within the cochlea or via waveguides from external optical sources. We investigated three waveguide designs made from OrmoComp ® , a polymer that cures through ultraviolet (UV) radiation. Waveguides were fabricated via injection molding and coated using dip-coating or thermal reflow or through aspiration of OrmoComp ® into a polyimide tubing that served as the cladding of the waveguide. The choice of fabrication technique directly determined the waveguides' total diameter: thermal reflow yielded ≈ 940 µm, dip-coating produced ≈ 306 µm, and aspiration resulted in ≈ 132 µm core diameter waveguides. Given the human cochlea's small size, we focused on analyzing the 306-µm and 132-µm waveguides, evaluating their optical performance (propagation and bending losses) and mechanical properties (bending stiffness and insertion forces). For the 100-µm core diameter waveguides, the propagation losses were 12.